Uncovering Visual Expression Driver on the Back of the Truck - Anthony Yudhie Mahendra Tumimomor; Ranang Agung Sugihartono; Pande Made Sukerta; Sunardi Sunardi (Blantika: Multidisciplinary Journal, 2026)
The present study seeks to elucidate the visual expressions of drivers manifested on the back of trucks. Visual expressions represent a unique phenomenon from budaya populer Indonesia's popular culture. The data in this study consists of images and sentences found on the rear of 100 trucks operating in Central Java, Indonesia. It is a common misconception that all visualizations on trucks are aesthetically pleasing; some individuals still harbor negative stereotypes toward them. The objective of this study is to ascertain the meaning and message that drivers seek to convey to the public. The present study employed an interpretive ethnographic methodology to understand the drivers' ways of thinking, their perspectives, and how they interact in their daily lives. The application of qualitative research with descriptive methods has been found to reveal visual elements, forms of expression, linguistic expressions, and the underlying meaning behind the creation of such visualizations. The results of this study illuminate the true message of these visual expressions, one of which is to showcase the conditions and outpourings of sentiment as experienced by truck drivers in reality.